Pemahaman Mengenai Undang-Undang dan Etika Profesi Akuntan Publik Terhadap Pemilihan Karier sebagai Akuntan Publik - Dita Ristya Damawati; Endang Masitoh Wahyuningsih; Yuli Chomsatu Samrotun (Jurnal Ilmiah Ekonomi Islam, 2016)
This research aim to know partially and simultaneously influence the understanding of the laws and ethics of the public accounting profession for a career as a public accountant election. This type of research is qualitative descriptive. The data source is the primary data. Population, sample and respondents were accounting students UNIBA Surakarta, sampling with random sampling. The research instrument used questionnaires in the validity and reliability. Data analysis method used descriptive test, classic assumption test including normality test, multicolinearity test, heteroscedasticity test, autocorrelation test for hypothesis testing using multiple linear regression with t test, F test and test determiasi (R2). H1 result t count > t table (3.591 > 1.991), and the significance 0.001 < 0.05 so Ha is received, so the understanding of the laws public accountant influence on the selection of a career as a public accountant. H2 result t count > t table (2.054 > 1.991), and the significance 0.043 < 0.05 so Ha is received, so the understanding of the public accounting profession ethics influence the election of a career as a public accountant. Test F, F count > F table (13.543 > 3.115) and significance < 0.05 (0.000 < 0.05), the Ha received so H3 result is that an understanding of the laws and ethics of the public accounting profession simultaneously affect the election as a career public accountant.Key words: Law, Public Accountant, Professional Ethics, Career Selection